Restricted permeability of rat liver for glutamate and succinate - Hems, R. (1968)
1. When rat liver slices were incubated aerobically with [U-(14)C]glutamate the concentration of (14)C within the slices remained lower (about 50%) than in the medium. The maximal concentration of (14)C in the liver was reached within minutes. In rat kidney-cortex slices by contrast, (14)C reached concentrations more than six times those of the medium. 2. In both liver and kidney (14)C appeared in the respiratory CO(2), indicating penetration of glutamate carbon into the mitochondria. In kidney slices the rate of glutamate oxidation per unit weight was about five times that in liver slices. 3. Taking into account the conversion of glutamate into glucose that occurs in the kidney but not in the liver, the flux rates of glutamate through the kidney were calculated to be about 15 times those through the liver when the external glutamate concentration was 5mm. 4. Anaerobically the glutamate concentrations in medium and tissue rapidly became equal in both liver and kidney. Thus the maintenance of concentration gradients depended on the expenditure of energy. 5. [U-(14)C]Succinate behaved similarly to glutamate. [U-(14)C]Serine was taken up more rapidly by the kidney than by the liver slices, but the concentrations reached in the liver did not remain below those of the medium. [(14)C]Urea was distributed evenly between medium and tissue water. 6. Incubation of liver slices with [(3)H]inulin indicated an extracellular space of liver slices of 26%. 7. When glutamate was generated within liver slices or the perfused liver on addition of oxaloacetate, pyruvate and a source of nitrogen, the concentration of glutamate in the tissue after 1hr. was 70–97 times that in the medium. Thus the exit of glutamate from the liver cell, like its entry, is restricted. This is borne out by measurements of the specific activity of extra- and intra-cellular glutamate on addition of [U-(14)C]glutamate medium. 8. Liver homogenates removed added glutamate and dicarboxylic acids 20–30 times as fast as did the perfused liver. 9. It is concluded that a major permeability barrier restricts the entry and exit through the outer liver cell membrane.